Request a call back

Asked by nishabr7 | 12 Sep, 2018, 20:12: PM

Let,
the present age of Mother = x years
the present age of daughter = y years
According to the 1st condition,
(x - 4)= 4(y - 4)
x - 4y = -12 ....(i)
According to the 2nd condition,
(x + 6)= 2(y + 6)
2x  - 5y = 18     ....(ii)
Multiply (i) by 2 , we get
2x - 8y = -24     ....(iii)
Subtracting (ii) form (iii), we get
-3y = - 42
y = 14
put y = 14 in (i), we get
x = 4y - 12 = 4 × 14 - 12 = 44

Therefore,

the present age of Mother = x years = 44 years
the present age of daughter = y years = 14 years
Answered by Yasmeen Khan | 14 Sep, 2018, 11:56: AM

## Application Videos

ICSE 9 - Maths
Asked by indrakalipandey333 | 25 Aug, 2024, 11:53: AM
ICSE 9 - Maths
Asked by bharatisarnaiktl | 17 Aug, 2024, 19:02: PM
ICSE 9 - Maths
Asked by ritikariya2010 | 04 Aug, 2024, 10:33: AM
ICSE 9 - Maths
Asked by shawpriyam9382 | 29 Jul, 2024, 16:45: PM
ICSE 9 - Maths
Asked by gamerthekushal | 27 Jul, 2024, 02:38: AM
ICSE 9 - Maths
Asked by jyotiharshu1304 | 22 Jul, 2024, 21:44: PM